Fulfilling Ethical Responsibility: Moving Beyond the Minimal Standards of Protecting Human Subjects from Research Harm - Hébert, James R; Satariano, William A; Friedman, Daniela B; Armstead, Cheryl A; Greiner, Allen; Felder, Tisha M; Coggins, Thomas A; Tanjasiri, Sora; Braun, Kathryn L (Progress in community health partnerships, 2015)
Problem: Rules for protecting human subjects, in place federally since 1974, have focused primarily on guarding against placing research subjects at social, physical, or psychological risk or violating their privacy and confidentiality. Nevertheless, high-risk communities are routinely subjected to “sins of omission,” which limit access to potentially significant research opportunities and result in the absence of studies that could confer high degree of community beneficence. Purpose of Article: To describe “sins of omission” and provide examples from the Community Networks Program Centers (CNPC) to illustrate how community-based participatory research (CBPR) can prevent them. Key Points: CBPR is an effective antidote to sins of omission. Activities undertaken by the CNPCs illustrate how adherence to CBPR principles can improve research access and outcomes. Conclusions: By working with community members as partners, we expand the concept of beneficence to include “community beneficence,” thus reducing the probability of “sins of omission.”